EFEKTIVITAS PENGGUNAAN VIDEO ANIMASI 3 DIMENSI BERBASIS LOCAL WISDOM DALAM PEMBELAJARAN QIRO’AH JAHRIYAH - Fadil, Muhammad; Ahmad Tarmizi; Muhammad Alfath Qaaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ qirā’ah jahrīyah proficiency in Grade VII at MTs Al-Mashri Pangkalan Balai remains low due to learning practices that rely heavily on conventional methods without the support of audio-visual media, resulting in insufficient accuracy in pronunciation, vowel length, intonation, and reading fluency, and ultimately falling below the minimum competency standards. Therefore, this study aims to determine the effectiveness of using three-dimensional animation videos based on local wisdom in improving students’ qirā’ah jahrīyah skills. This research employed a mixed-method approach with a pretest–posttest design, in which qualitative data were collected through observations and interviews, while quantitative data were obtained through pre-tests and post-tests, with the sample selected using purposive sampling. The results show a significant improvement in students’ reading performance after the implementation of the 3D animated video, as indicated by the increase in the post-test mean score of 85.32 compared to the pre-test mean score of 63.72. The normality test confirmed that the data were normally distributed with a significance value greater than 0.05, while the t-test revealed a significant difference between students’ abilities before and after the treatment. Additionally, the N-Gain score fell into the moderate to high category, indicating effective improvement in learning outcomes. Thus, the use of three-dimensional animation videos based on local wisdom has a positive and effective impact on enhancing the qirā’ah jahrīyah skills of Grade VII students at MTs Al-Mashri Pangkalan Balai.